2008
DOI: 10.1590/s1806-83242008000200003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro assessment of the effectiveness of whitening dentifrices for the removal of extrinsic tooth stains

Abstract: This in vitro study evaluated the effectiveness of whitening dentifrices for the removal of extrinsic tooth stains. Twenty dental blocks (4 x 4 mm), including enamel and dentine, removed from freshly extracted bovine incisors, were randomly divided into 4 groups: G1 -distilled water, G2 -Colgate, G3 -Crest Extra Whitening and G4 -Rapid White. In all specimens, the dentin was covered with colorless nail polish, and the enamel was left exposed. Next, the specimens were immersed in a solution of black tea, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
77
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(87 citation statements)
references
References 16 publications
1
77
1
8
Order By: Relevance
“…Brushes with soft bristles and rounded edges (TEK ® , Johnson & Johnson ® , São Paulo, Brazil) were fixed to the apparatus and kept alongside the samples, using slurry of Colgate ® Total 12 Clean Mint dentifrice with distilled water in a ratio of 1:3 by weight 20 . Simulated brushing was performed with a linear movement, speed of 4.5 cycles per second, a cycle understood as being the complete back-and-forth movement of the toothbrush.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brushes with soft bristles and rounded edges (TEK ® , Johnson & Johnson ® , São Paulo, Brazil) were fixed to the apparatus and kept alongside the samples, using slurry of Colgate ® Total 12 Clean Mint dentifrice with distilled water in a ratio of 1:3 by weight 20 . Simulated brushing was performed with a linear movement, speed of 4.5 cycles per second, a cycle understood as being the complete back-and-forth movement of the toothbrush.…”
Section: Methodsmentioning
confidence: 99%
“…Simulated brushing was performed with a linear movement, speed of 4.5 cycles per second, a cycle understood as being the complete back-and-forth movement of the toothbrush. Each experimental group (1) Listerine ® Vanilla Mint, (2) Plax ® without alcohol, (3) Oral B ® alcohol-free, (4) alcohol 96, and (5) distilled water, was subjected to 02 intercalated time periods of 5,000 brushing cycles equal to a total of 10,000 cycles (representing the total time of 1 year of brushing) each time period performed in 40 minutes 20 . At the end of each cycle, the samples were washed under running water to remove the toothpaste.…”
Section: Methodsmentioning
confidence: 99%
“…9 Their stain-removal ability is related to the large quantity of abrasives in their formulation, which remove superficial extrinsic stains. 10 The active components of tooth whitening dentifrices include enzymes that break down the organic molecules of biological film. Additionally, abrasives such as alumina, dicalcium phosphate dihydrate and silica are also present in the formulation to promote stain-removal.…”
Section: Whitening Dentifricesmentioning
confidence: 99%
“…11 A number of studies have been published to measure changes in tooth color after regular whitening toothpaste use. [10][11][12] Generally, when whitening dentifrices are compared to non-whitening toothpastes the results have demonstrated that their use can remove and/or prevent extrinsic tooth stains. 1,10,13,14 Although whitening toothpastes can prevent ex-trinsic tooth stains, the whitening effect obtained seems not to be clinically significant.…”
Section: Whitening Dentifricesmentioning
confidence: 99%
See 1 more Smart Citation